High Levels of Zinc Stimulate Different Aspects of Immune System in Broiler Chicks - Sajadifar , S.; Miranzadeh, H. (International Journal of Poultry Science, 2013)
In this study experimental treatments were as follows: broilers fed with 40 mg/kg Zn (A), broilers fed with 40 mg/kg Zn and vaccinated against coccidiosis (B), broilers fed with 120 mg/kg Zn (C),broilers fed with 120 mg/kg Zn and vaccinated against coccidiosis (D), broilers fed with 200 mg/kg Zn (E), broilers fed with 200 mg/kg Zn and vaccinated against coccidiosis (F). Average body weight gain, average daily feed intake and feed conversion ratio were obtained on d 21 and 42. At 2, 22, 32, 42 days of age, the blood serums were tested for antibody titer against Newcastle disease vaccination, using the standard Haemagglutination Inhibition test. On day 42 total protein, albumin, globulin (by an automated analyzer), weights of spleen and bursa of fabricius (on a relative live weight basis) and total leukocytes (using a hemocytometer) were measured. No dietary treatment significantly altered average daily feed intake, body weight gain and feed conversion ratio at days 21 and 42. The highest weights of spleen and bursa of fabrecius were observed at the combination of highest level of zinc and coccidiosis vaccine. At 32 d, treatment D and at 42 d, treatments D, E and F had the highest antibody titer against Newcastle disease vaccination. It is concluded that the treatments B, C, D, E and F showed significant (p<0.05) increase in white blood cell count as compare to control group (treatment A). Treatment F significantly improved total protein and albumin as compare to treatment A (p<0.05). Additional levels of zinc could be considered as natural promoter to increase different aspects of immune system without any harmful effect on performance traits.